Adsorption of natural dye on bamboo yarn - Logapriya, Logamaintan (2015)
Long-established usage of synthetic dye causes detrimental effects not only to the environment but to human as well as these synthetic dyes are often non biodegradable and have high toxic content. Consequently, various researches are being conducted on the extraction of natural dye and its application in textile industries, indicating that natural dye serves as a feasible alternative to synthetic dye. Usage of natural dye not only has caught the attention of textile industries but also material scientist and engineers long ago. In this current study, pitaya peel and turmeric have been selected as the sources for natural dye. Experiments will be conducted to determine the adsorption level using spectrophotometer aided with several calculations for maximum adsorption using adsorption isotherm. The process of solvent extraction using water as solvent is applied in this study to extract the dye from the pitaya peel and turmeric. The usage of mordant is also needed here to ensure the dye fast on the bamboo yarn. The concentration of total betacyanin and curcumin was measured by using a UV-Vis spectrophotometer and was also used as a measure of the degree of extraction. The rate of adsorption is studied by using different 'concentrations of dye extracted by using the dilution method. Three major parameters studied in this research includes the rate of adsorption on bamboo yarn using varied dye concentrations, length of time required for the process of adsorption on bamboo yarn and effectiveness of adsorption on bamboo yarn. Result obtained from this study shows that the rate of adsorption increases as the concentration of dye increases. Also, the time required for the process of adsorption on bamboo yarn increases in the same pattern due to the potential of bamboo yarn to adsorb the dye but decreases once the equilibrium time has been reached.